Advantages and Disadvantages of Electronic Cigarettes (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Electronic cigarettes (ECs) have been present on the consumer market for over a decade, and the number of related scientific publications in the PubMed database has now exceeded seven thousand. Despite the number of publications, there is still no consensus in the scientific community regarding their safety. However, it should be emphasized that a comparison of equivalent quantities of tobacco smoke and the aerosol produced from e-cigarettes showed that there was a significantly lower quantity of toxic compounds in the aerosol compared with the tobacco smoke. Therefore, the use of ECs could be seen as a way of reducing the health damage to cigarette smokers who cannot or are unwilling to quit using conventional methods. In addition, randomized studies are emerging suggesting that ECs could be useful in smoking cessation. On the other hand, ECs are now widely used among adolescents and may pose a serious risk of future nicotine dependence and health problems in this population, as they counteract their advantages in the population gained from smokers who quit using them. Therefore, as most authors stress, further research that will convincingly resolve the current controversies is needed. Clinicians urgently need evidence-based knowledge to better inform their patients about the use of these emerging tobacco products as a harm-reduction strategy, and regulators should regulate these products in ways that best serve public health, especially taking the youth population into account.